ETIKA DAN SOLIDARITAS SOSIAL DALAM GERAKAN BERBAGI NASI DI BANDUNG: MEMBANGUN JIWA SOLIDARITAS MASYARAKAT KOTA BANDUNG - Danang Nugroho; Nabila Citra Ardhia; Nadila Citra Ardina; Rika Aprilianti; Raihan Nur Fauzi (JURNAL ILMIAH RESEARCH AND DEVELOPMENT STUDENT, 2024)
This research aims to determine the ethics and social solidarity carried out in the Sharing Rice movement in Bandung to build high social solidarity, especially in the community in Bandung City. In this research, data collection was used using indirect research methods. Data analysis starts from understanding the theory and case studies, then conclusions and outlines are drawn from the case studies. The results of this research show that the ethics and social solidarity that exist in the case of the Sharing Rice movement are very good and this is also the right opportunity and means for the community, especially the city of Bandung, who want to increase their spirit of solidarity, either on social media or directly.